The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1074/jbc.m114.578187
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Enzymatic Reduction of Truncated Hemoglobin N of Mycobacterium tuberculosis

Abstract: Background:The HbN of Mycobacterium tuberculosis carries a potent nitric-oxide dioxygenase activity despite lacking a reductase domain. Results:The NADH-ferredoxin reductase system acts as an efficient partner for the reduction of HbN. Conclusion:The interactions of HbN with the reductase are modulated by its CD loop and the Pre-A region. Significance: The present study provides new insights into the mechanism of electron transfer during nitric oxide detoxification by HbN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Herein we have shown that THB1 is very efficiently reduced by NR, which contains FAD as a cofactor (Figure 4d). It is noteworthy that GlbN from Mycobacterium tuberculosis can be reduced in vitro at a concentration and velocity similar to those of CrTHB1 by the NADH ferredoxin/flavodoxin reductase system from E. coli (Singh et al, 2014). NR takes electrons from NAD(P)H to reduce nitrate or alternatively to transfer these electrons to other acceptors from FAD (diaphorase activity).…”
Section: Discussionmentioning
confidence: 99%
“…Herein we have shown that THB1 is very efficiently reduced by NR, which contains FAD as a cofactor (Figure 4d). It is noteworthy that GlbN from Mycobacterium tuberculosis can be reduced in vitro at a concentration and velocity similar to those of CrTHB1 by the NADH ferredoxin/flavodoxin reductase system from E. coli (Singh et al, 2014). NR takes electrons from NAD(P)H to reduce nitrate or alternatively to transfer these electrons to other acceptors from FAD (diaphorase activity).…”
Section: Discussionmentioning
confidence: 99%
“…The microbe-derived HbN decomposes NO produced by macrophages and neutrophils so the bacterium may survive within the cytosol. HbN acts as a NO dioxygenase despite the absence of a true reductase domain [115]. HbN expression intensifies once the bacterium enters the WBC.…”
Section: Use Of Hemoglobin By Microbesmentioning
confidence: 99%
“…O 2 and NO tunnels and a nitrate egress pathway have been suggested to play roles in the NOD function of the truncated HbN from Mycobacterium tuberculosis ( 22 , 23 ). A long hydrophobic tunnel that runs parallel to the H helix and perpendicular to the heme plane is thought to allow NO ( 22 , 24 , 25 ), or O 2 ( 16 , 24 , 26 ), to access the distal heme reaction chamber, while a short tunnel formed between the G and H helices at the AlaG5 and LeuH8 residues allows O 2 ( 22 ), or NO ( 24 , 26 , 27 ), to access the distal heme pocket. Moreover, movement of PheE15 caused by O 2 binding to the ferrous heme and TyrB10-GlnE11 hydrogen-bonding interactions ( 28 ) may function as a gate, in cooperation with LeuG8, that controls NO access to the heme ( 22 , 25 , 29 , 30 , 31 ).…”
mentioning
confidence: 99%